PENGARUH SHARED LEADERSHIP TERHADAP BERBAGI PENGETAHUAN DALAM TIM - Adnan Effendi (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2018)
The study sets out to examine the effect of shared leadership on knowledge sharing within the team. Data was collected through a survey using a questionnaire to 157 respondents from 34 students organization in UNS and UGM. This study applies the regression to investigate the research model. The results showed that the shared leadership has a significant positive effect on knowledge sharing within the team. The implications of the review for future research and practices are also discussed.